The Tumor Microenvironment of High Grade Serous Ovarian Cancer - Kenneth P. Nephew (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Special Issue on high grade serous ovarian cancer (HGSOC) and the contribution of the tumor microenviroment (TME) consists of reviews contributed by leaders in the OC field. As HGSOC metastases have a highly complex TME, there is an urgent need to better understand the TME in general, its distinct components in particular, and the role of the TME in the context of disease recurrence and development of chemoresistance. The Special Issue incorporates the current understanding of the different parts of thd TME components, including the cancer cells themselves, the cells surrounding the cancer cells or stromal cells, and the cells of the immune system, which are attracted to the site of metastases. In addition to these cells of the TME, the role of various cellular factors made by the cells of the TME are also the subject of the reviews. In addition, reviews in this Special Issue cover the complex relationships between the molecular mechanisms of HGSOC progression, including genomic, epigenomic and transcriptomic changes and changes in the immune cell landscape, as these may provide attractive new molecular targets for HGSOC therapy.